Women-based policies and legal frameworks in Ethiopia since 1991: Women’s political empowerment analysis: Women-based policies and legal frameworks - Degu, Zeynie Chekol; Hando, Flimon Hadaro; Gebre, Hanna Tegegn (Ethiopian Journal of Social Sciences, 2024)
A comprehensive policy framework and proper implementation are necessary to ensure women's empowerment, including gender equality in decision-making positions. This research examined selected Ethiopian women-based legal frameworks from the perspective of women's political empowerment. It aimed at assessing the extent to which the policies in place improve women's political empowerment. This research primarily utilizes a qualitative approach that draws on relevant primary and secondary data sources. The study used Variety of Democracy Women’s Political Empowerment Indicators (V-Dem Index) to review the content of the selected legal frameworks of Ethiopia since 1991. Using the indicators, the 1995 Constitution of the Federal Democratic Republic of Ethiopia, the 1993 National Policy on Ethiopian Women, and other two strategy documents were specifically examined. The results revealed that existing women-based policies and strategies in Ethiopia do not fully recognize and comprehensively address the key indicators of women's political empowerment. This has also an adverse impact on the political representation of women in Ethiopia. Thus, reform efforts to comprehensively include women’s political empowerment indices during the development and implementation of policy and legal frameworks are still policy concerns in Ethiopia. Indeed, policy reform measures that consider women's perspectives and interests should be developed in order to enhance women's genuine decision-making roles.